LITERATURE REVIEW: HUBUNGAN PERILAKU CARING DAN KINERJA PERAWAT DENGAN TINGKAT KEPUASAN PELAYANAN KEPERAWATAN PADA PASIEN DI RUANG RAWAT INAP - Angkasa, Moh. Projo; Maela, Naziatul; Martyastuti, Nonik Eka (JURNAL LITBANG KOTA PEKALONGAN, 2020)
The problem in the nursing profession in Indonesia is nurses still have not carried out the caring role professionally in providing nursing care to clients. In providing nursing care it is not uncommon to be a target of patient dissatisfaction. The quality or satisfaction of nursing service itself cannot be separated from the performance of nurses. The aim of this literature review to determine the correlation between caring attitude and nurse performance with satisfication of nursing services in the inpatient room. The literature review uses a narrative method. This research article was obtained from Google schoolar, portal garuda and journal PPNI by using inclusion and exclusion criteria. Keywords used in the search were nurse caring attitude, nurse performance, client satisfaction, and inpatient room. Based on 10 journals, it was found that a person's internal factors can affect their performance where the better of nurses caring behavior in nursing services to patients, the better of patient satisfaction level with nursing services. There are correlation of caring attitude and nurse’s performance with patient satisfaction in inpatient room. It means there is good caring attitude and good performance of nurses will increase patient satisfaction. Keywords: Nurse caring attitude, nurse performance, client satisfaction, inpatient room